2014
DOI: 10.1159/000365967
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Gastrointestinal Bleeding with Dabigatran: A Head-to-Head Comparative Study with Rivaroxaban

Abstract: Introduction: The risk of gastrointestinal (GI) bleeding of dabigatran and rivaroxaban is relatively unexplored. The aim of our study was to compare this risk in both drugs. Methods: We examined the medical records of patients on either dabigatran or rivaroxaban from October 2010 to April 2013 in two hospitals. Results: A total of 374 patients (147 rivaroxaban vs. 227 dabigatran) were identified. GI bleeding occurred in 5.3% in the dabigatran when compared to 4.8% in the rivaroxaban group (p = 0.8215). Multiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 32 publications
(49 reference statements)
0
32
0
1
Order By: Relevance
“…Various risk factors for colonic diverticular bleeding have been reported, including the use of nonsteroidal anti-inflammatory drugs (NSAIDs), antiplatelet drugs, concomitant arteriosclerotic diseases, such as hypertension and diabetes mellitus, and cardiovascular and cerebrovascular diseases [3,4,5,6,7,8]. Female sex, warfarin use, and chronic kidney disease reportedly increase the risk of a transfusion requirement, while advanced age and NSAID use increase the risk of prolonged hospitalization [9,10]. Colonoscopy is applied for both diagnosis and treatment of colonic diverticular bleeding.…”
Section: Introductionmentioning
confidence: 99%
“…Various risk factors for colonic diverticular bleeding have been reported, including the use of nonsteroidal anti-inflammatory drugs (NSAIDs), antiplatelet drugs, concomitant arteriosclerotic diseases, such as hypertension and diabetes mellitus, and cardiovascular and cerebrovascular diseases [3,4,5,6,7,8]. Female sex, warfarin use, and chronic kidney disease reportedly increase the risk of a transfusion requirement, while advanced age and NSAID use increase the risk of prolonged hospitalization [9,10]. Colonoscopy is applied for both diagnosis and treatment of colonic diverticular bleeding.…”
Section: Introductionmentioning
confidence: 99%
“…[16] However, the authors used medical records from only two hospitals and did not examine the risk of bleeding by dose of anticoagulant separately. [16] Because the risk of bleeding varies by the strength of anticoagulant, it is also necessary to separately examine the risk of bleeding by dose.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, another study including 556 consecutive patients showed both drug rivaroxaban and dabigatran to be effective and safe compared to warfarin [11]. Another head-to-head comparison on the other hand showed dabigatran and rivaroxaban to have a higher bleeding risk in the first 40 days, but dabigatran was not associated with an increased risk of GI bleeding [12]. …”
Section: Discussionmentioning
confidence: 99%